Design Of Temperature System On The Electrical Tank Heater Using PLC - Dewi, Astrie Kusuma; Sugirto, Ihrom; Hamdani, Chalidia Nurin; Septiani, Natasya Aisah (Politeknik Negeri Lhokseumawe, 2024)
A temperature control system is required in any situationthat requires a certain temperature to remain stable.Likewise, in the electrical processtank heater that requires a control system, because the temperature is notby the set value will cause overheating it,causing the product temperature is not as desired and can even causea dangerous explosion. In this project, the design is carried outtemperature control on the prototype electrical tank heater usingPLC Nano V5.2 as the controller, and the control method used is fuzzy Sugeno.Fuzzy logic has a value of obscurity and obscuritybetween right and wrong and control systems. Membership value may varyfrom 0 to 1. This means a situation can have two values, “yes or no” and